Pengaruh Pembelajaran Kooperatif Terhadap Hasil Belajar Keterampilan Chest Pass Bola Basket di SMPN 1 Rengasdengklok - Setiadi Ramdani; Rizki Aminudin; Dayat Hidayat (Jurnal Literasi Olahraga, 2020)
The aim of this research is for identifying the effect of cooperative learning model towards the learning outcome of basketball chest pass skill on 7th grade students in SMPN I Rengasdengkolk. In order to answer the research questions, the writer utilize quantitative approach with an experiment method. This research is implemented in SMPN I Rengasdengklok and lay hold of VII I class as a research sample which has 43 students as respondents. There are three stages of this research: pre-test, treatment, and post-test. Pre-test is implemented for recognizing the learning outcome of basketball chest pass skill before applying the treatment. After pre-test has been implemented, the researcher applies the treatment to the respondents through cooperative learning method. After the treatment, the researcher gives post-test in order to analyze the effect of cooperative learning model towards the learning outcome of basketball chest pass skill on the respondents. The research is analyzed by T-test. The result of research indicates that cooperative learning model towards the learning outcome of basketball chest pass skill on 7th grade students in SMPN I Rengasdengklok with the result of T-hitung 21,75 is compared with T-table 2,018.